Need of L-Hospital's Rule

Calculus Level pending

With the following flawed work out I strived to prove that

lim x 0 x x = \lim_{x \to 0} x^x= \infty

Which of the following step is made firstly incorrect?

Let a function f ( x ) = x x f(x) = x^x , where x > 0 x>0 .

Step :

  1. lim x 0 + f ( x ) \displaystyle \lim_{x \to 0^+} f(x)
  2. lim x 0 + x x \displaystyle \lim_{x \to 0^+} x^x
  3. lim x 0 + e log x x \displaystyle \lim_{x \to 0^+} e^{\log x^x}
  4. lim x 0 + e x log x \displaystyle \lim_{x \to 0^+} e^{x\log x}
  5. e lim x 0 + ( x log x ) e^{\lim_{x \to 0^+}(x \log x)}
  6. e lim x 0 + d d x ( x log x ) e^{\lim_{x \to 0^+} \frac d{dx}(x \log x)}
  7. e lim x 0 + ( 1 + log x ) e^{\lim_{x \to 0^+} (1+\log x)}
  8. e e^\infty
  9. \infty (Hence proved)
7 5 2 8 4 6 1

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

If we apply L'Hospital, we need to differentiate the denominator as well!

So Step 6 is wrong!

lim x 0 + ( x log x ) = lim x 0 + log x 1 / x = lim x 0 + d d x log x d d x 1 x \lim_{x \to 0^+} (x \log x) = \lim_{x \to 0^+} \frac{ \log x}{1/x} =\lim_{x \to 0^+} \frac {\frac{d}{dx} \log x} { \frac {d} {dx} \frac{1} {x}}

This is how we will apply L'Hospital

It is not clear to me how L'hopital is involved.

Instead, the error is because of (to be filled in).

Calvin Lin Staff - 4 years, 3 months ago

If we differentiate the denominator as you mentioned which carries constant 1 1 results to so better is to mentioned that we need to get that form so that L-hopital rule is involved as e lim x 0 ( l o g x 1 / x e^{\lim_{x→0}(\frac{logx}{1/x}} .

Naren Bhandari - 4 years, 3 months ago

Log in to reply

Ah ic. Could you make that usage of L-hopital's rule much clearer?

Otherwise, it seems to me that you're saying lim f ( x ) = lim f ( x ) \lim f(x) = \lim f'(x) , where f ( x ) = x log x f(x) = x \log x (and that's the error that I thought was happening).

Calvin Lin Staff - 4 years, 3 months ago

  1. lim x 0 + f ( x ) \displaystyle \lim_{x \to 0^+} f(x)
  2. lim x 0 + x x \displaystyle \lim_{x \to 0^+} x^x
  3. lim x 0 + e log x x \displaystyle \lim_{x \to 0^+} e^{\log x^x}
  4. lim x 0 + e x log x \displaystyle \lim_{x \to 0^+} e^{x\log x}
  5. e lim x 0 + ( x log x ) e^{\lim_{x \to 0^+}(x \log x)}
  6. e^{\lim_{x \to 0^+} (\frac{logx}{1/x})
Now we can make the usage of L-hopital rule as the form is \frac{∞}{∞}

  1. e lim x 0 + x 1 x 2 e^{\lim_{x \to 0^+} \frac {x^{-1}}{-x^{-2}}}

  2. e l i m x 0 + ( x ) e^{lim_{x \to 0^+} (-x) }

  3. e 0 = 1 e^0 = 1

Naren Bhandari - 4 years, 3 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...